The lion king - Hover, M.; Barnes, Judy; Cuddy, Robbin (Racine, Wis. : Western Pub. Co., 1994)
Simba, the first cub born to the Lion King Mufasa and his queen Sarabi, runs away from the Pride Lands, believing he caused his father's death, but when he is made to realize his responsibilities, he returns to reclaim his rulership over the animal kingdom from his evil uncle Scar.
"A Golden book, New York."
At head of title: Disney's
4.8
K-3
K-3
Keywords: Lions -- Fiction; Animals -- Fiction; Kings, queens, rulers, etc. -- Fiction; Lions -- Fiction; Animals -- Fiction; Kings and rulers -- Fiction